PARTISIPASI PEMELIHARAAN BENDUNGAN BATUJAI KABUPATEN LOMBOK TENGAH: Participation In The Maintenance Of The Batujai Dam, Central Lombok District - Yamin, Muhamad; Aminullah, Aminullah; Dharma S., Bagus Widhi; Seventilofa, I Gusti Ngurah Octova; Ardika, Gede Tusan; Titawati, Titin; Ramli, Ramli; Dewi, Ni Made Nia Bunga Surya; Apriani, Titin; Loilewen, Aline Febriany (Al-Amal: Jurnal Pengabdian Masyarakat, 2024)
The purpose of this service is to participate in the maintenance of the Batujai dam, Central Lombok Regency. The method for carrying out this service is to be directly involved in dam maintenance, especially regarding gates, channels, vegetation, walls and flood control. The service carried out is limited to light, simple and short maintenance such as maintenance of secondary channel sluice gates. Sluice gate maintenance is limited to cleanliness and lubrication. Other maintenance that can be carried out is related to the vegetation around the dam. Large amounts of vegetation also cannot be carried out due to time, cost and equipment constraints. Maintenance of walls, channels and irrigation systems requires time, money and adequate tools so it cannot yet be realized